Participation rights in practice: what are the power bases of worker representatives at the board? - Conchon, Aline; Waddington, Jeremy (Brussels, 2015)
"Workers’ right to be represented on the board (of directors, or supervisory board) of their company is so widespread in Europe that it is deemed a core element of the European social model. Yet, very little is known about how those participation rights operate in practice.